2022
DOI: 10.1111/jnc.15585
|View full text |Cite|
|
Sign up to set email alerts
|

Amyloid processing in COVID‐19‐associated neurological syndromes

Abstract: SARS‐CoV‐2 infection can damage the nervous system with multiple neurological manifestations described. However, there is limited understanding of the mechanisms underlying COVID‐19 neurological injury. This is a cross‐sectional exploratory prospective biomarker cohort study of 21 patients with COVID‐19 neurological syndromes (Guillain–Barre Syndrome [GBS], encephalitis, encephalopathy, acute disseminated encephalomyelitis [ADEM], intracranial hypertension, and central pain syndrome) and 23 healthy COVID‐19 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…We have recently demonstrated that protein depletion and related loss-of-function is more pathologically important than plaque burden in AD, where high levels of soluble Aβ42 in the CSF were associated with preserved cognition even in individuals with high amyloid plaque burden (22). Depletion of soluble Aβ42 in the CSF, which is a recognized feature of many neurodegenerative disorders, has been demonstrated in patients with post-COVID neurological symptoms (59), suggesting that protein depletion post-infection might contribute to the neurological symptoms. Further studies examining the levels of more CSF proteins in post-COVID patients compared to controls could reveal additional information on this potential pathophysiological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that protein depletion and related loss-of-function is more pathologically important than plaque burden in AD, where high levels of soluble Aβ42 in the CSF were associated with preserved cognition even in individuals with high amyloid plaque burden (22). Depletion of soluble Aβ42 in the CSF, which is a recognized feature of many neurodegenerative disorders, has been demonstrated in patients with post-COVID neurological symptoms (59), suggesting that protein depletion post-infection might contribute to the neurological symptoms. Further studies examining the levels of more CSF proteins in post-COVID patients compared to controls could reveal additional information on this potential pathophysiological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Nima Rezaei first mainly focused on neurological complications of COVID-19 ( 41 , 42 ) and then shifted to the neurological side effects of COVID-19 vaccination ( 43 ). Henrik Zetterberg focused on exploring potential neurochemical biomarkers and underlying mechanisms of COVID-19-related neuropathy ( 44 46 ), Tom Solomon was the most cited author because he published two articles in Lancet Neurology ( 3 ) and Lancet Psychiatry ( 5 ) that give readers a comprehensive understanding of the neurological and neuropsychiatric complications of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients (15%) had mildly elevated protein. CSF Aβ42 and Aβ40 have been described as abnormal in neuro-PASC, indicating impaired amyloid processing suggesting a possible degenerative component in this population [165]. Serum neurofilament, a marker of neuronal damage, has been shown to be elevated in hospitalized COVID-19 patients, although this test is not widely available for clinical use due to need for specialized lab equipment [166].…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%